The Directionality of Vowel Elision in Picard - Cardoso, Walcir (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2001)
This paper offers an analysis for the domain-sensitive process of Vowel Elision in Picard, whose directionality depends on the interaction of a variety of phonological, morphosyntactic and semantic factors. By adopting the framework of Optimality Theory, I propose an analysis in which constraints are decomposable into their domain-specific counterparts. The main advantage of such an approach to domain-driven phenomena is its intrinsic assumption that only one grammar (or constraint ranking) is responsible for domain-driven variation cross-linguistically.